2016
DOI: 10.1007/s00429-016-1217-x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular architecture and transmitter phenotypes of neurons of the mouse median raphe region

Abstract: The median raphe region (MRR, which consist of MR and paramedian raphe regions) plays a crucial role in regulating cortical as well as subcortical network activity and behavior, while its malfunctioning may lead to disorders, such as schizophrenia, major depression, or anxiety. Mouse MRR neurons are classically identified on the basis of their serotonin (5-HT), vesicular glutamate transporter type 3 (VGLUT3), and gamma-aminobutyric acid (GABA) contents; however, the exact cellular composition of MRR regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 66 publications
6
60
1
Order By: Relevance
“…Thus, DRL displays fairly specific connections, for example, with the IP and MnR, present findings (Lima et al, ), and has been selectively implicated in social stress (Crawford, Rahman, & Beck, ) and panic behavior (Johnson, Hollis, Moratalla, Lightman, & Lowry, ). Furthermore, our combined immunohistochemical/retrograde tracing findings suggest that all major neuronal populations present in the DR/MnR (Hioki et al, ; Sos et al, ) provide inputs to the LDTg, with a predominance of glutamatergic and GABAergic neurons, the later indicated indirectly by the elevated number of single labeled CTb neurons. An explicit role of the MnR in mechanisms of fear/anxiety has only been fully recognized during the last two decades.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Thus, DRL displays fairly specific connections, for example, with the IP and MnR, present findings (Lima et al, ), and has been selectively implicated in social stress (Crawford, Rahman, & Beck, ) and panic behavior (Johnson, Hollis, Moratalla, Lightman, & Lowry, ). Furthermore, our combined immunohistochemical/retrograde tracing findings suggest that all major neuronal populations present in the DR/MnR (Hioki et al, ; Sos et al, ) provide inputs to the LDTg, with a predominance of glutamatergic and GABAergic neurons, the later indicated indirectly by the elevated number of single labeled CTb neurons. An explicit role of the MnR in mechanisms of fear/anxiety has only been fully recognized during the last two decades.…”
Section: Discussionmentioning
confidence: 70%
“…For this purpose, injections of retrograde and anterograde tracers were made into the LDTg, LHb, IP, or MnR. Since LDTg (Wang & Morales, ), IP (Quina et al, ), and MnR (Sos et al, ) are now known to be neurochemically heterogeneous, we also characterized the transmitter phenotype of the projections between LDTg‐IP, and MnR‐LDTg. To this end, we combined retrograde tracing from IP or LDTg with immunofluorescence staining for choline acetyltransferase (ChAT), serotonin (5‐HT), and the Type 3 vesicular glutamate transporter (VGLUT3), and also with in situ hybridization for glutamate decarboxylase 67 kDA (GAD67), as well as the Type 2 vesicular glutamate transporter (VGLUT2).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it was not clear which neuronal pathway orchestrates the coordinated activation of these networks. Although the MRR was known to play a central role in processing negative experience (15,54), its known cell types did not project to the LHb, and the transmitter phenotypes and targets of almost 25% of the MRR neurons were not even known (22).…”
Section: Discussionmentioning
confidence: 99%
“…The number of Pet-1+ cells without detectable 5-HT identity was reported to be about 27% in the MRN while in the B7 and B6 portions of the DRN this number was only 1% (Pelosi et al, 2014). These findings were interpreted as evidence that not all Pet-1+ cells are 5-HT neurons (Sos et al, 2016). However, recent single cell RNA seq studies have revealed that all of the single Pet-1+ cells sequenced in the DRN and MRN express Tph2 , although some had a much lower number of Tph2 reads that other Pet-1+ cells (Okaty et al, 2015).…”
Section: Maturation Of Pet-1+/5-ht Neuronsmentioning
confidence: 99%